The feasibility and challenge of using administrative data: a case study of historical prisoner surveys. Issue 1 (2nd January 2022) - Quinn, Anthony; Denney, David; Hardwick, Nick; Jalil, Rahul; Meek, Rosie
ABSTRACT: The benefits of government administrative data are well-established, but research has not examined processes by which these data can be identified, organised and governed in line with ethical considerations. This is an important undertaking given the potential benefits of robust administrative data, especially at a time when the collection of primary data has been made more challenging due to COVID-19 restrictions. We use principles of Big Data to characterise a large operational data set comprised of responses from a prisoner survey about experiences of detainment in England and Wales. These findings are discussed in relation to future research with administrative data and the value that historical survey data can provide to various beneficiaries.